Reflections on the First Decade of Multiparty Politics in Tanzania - Msekwa, Pius. (Dar es Salaam Nyambari Nyangwine Publishers, 2014)
Reflections on the First Decade of Multiparty Politics in Tanzania; addresses the political system in the country by comparing the mono-party period and the multiparty period, the functioning of parliament and its operation under the multiparty system and the challenges of the two-government structure of the union.
Includes index
Keywords: Multiparty Politics